(untitled) (The Review of Diabetic Studies, 2025)
Purpose: This systems-level review examines how Emergency Medical Service (EMS) routing strategies and paramedic response pathways influence clinical, operational, and survival outcomes in road traffic accidents (RTAs). Methods: A structured review of peer-reviewed literature published from 2016 onward was conducted using major medical and transport databases. Studies addressing EMS dispatch, travel route optimization, response time, navigation technologies, and paramedic-led prehospital interventions in RTAs were included. Results: Evidence consistently shows that optimized routing and reduced response time are strongly associated with improved trauma survival, faster scene stabilization, and reduced secondary complications. Advanced dispatch algorithms, GPS-enabled navigation, and real-time traffic integration significantly enhance EMS efficiency. System-level coordination between dispatch centers, paramedics, and trauma facilities emerged as a critical success factor. Conclusion: EMS routing is not merely a logistical function but a determinant of trauma outcomes. Integrating intelligent routing systems with paramedic decision-making can substantially reduce mortality and morbidity from RTAs. Policymakers and EMS leaders should prioritize system-level investments in routing technologies and workforce training.